Paleolimnological Assessment Of Environmental Change In Bukit Merah Reservoir Perak, Malaysia - Simeon, Adole Akogwu (2024)
The aim of this study was to reconstruct historical environmental changes in Bukit Merah Reservoir using geochemical and diatom proxies. Two sediment cores, BMRI and BMR2, were collected, sectioned at 1cm intervals, and analysed for 210Pb chronology, metal(loid)s (arsenic, cadmium, copper, lead, zinc, and iron), nutrient levels (total nitrogen, total organic carbon, and total phosphorus), along with diatom composition using standard methods. The CRS (constant rate of 210Pb supply) model dated the oldest sediments back to 1985 ± 34 years AD (22.5-24.5). Stratigraphic analysis of metal(loid) pollution fluxes revealed variations over time. In the 1980s, lower fluxes were observed for arsenic (As), copper (Cu), zinc (Zn), and iron (Fe) at 29 mg cm-2 yr-1, 3.0 mg cm-2 yr-1, 75 mg cm-2 yr-1, and 148 mg cm-2 yr-1, respectively, which indicated a reduced rate of deposition of these metals during this period. These values contrasted with higher fluxes in the 2000s: 43 mg cm-2 yr-1 for As, 9.0 mg cm-2 yr-1 for Cu, 120 mg cm-2 yr-1 for Zn, and 2003 mg cm-2 yr-1 for Fe. indicating a significant increase in the accumulation of these elements during this period. Lead (Pb) fluxes were minimal in the 1980s (33.0 mg cm-2 yr-1), peaked at 56.0 mg cm-2 yr-1 in the 1990s, while cadmium (Cd) exhibited a similar pattern with minimal flux in the 1980s (2.20 mg cm-2 yr-1) and peak flux in the 1990s (3.60 mg cm-2 yr-1). The depositional fluxes of nutrients displayed fluctuations over time as well. Total phosphorus (TP) flux was lowest between 1985-1990 (1.56 mg cm-2 yr-1) and highest between 2016 and 2018 (3.98 mg cm-2 yr-1).